Prediksi Tingkat Kunjungan Pasien dengan Menggunakan Metode Monte Carlo - Aldo Eko Syaputra; Yofhanda Septi Eirlangga (Jurnal Informasi dan Teknologi, 2022)
The increase in the number of patient visits that often occur at community health centers / puskesmas has caused some activities in health services to be slightly hampered, disturbed and less than optimal, resulting in some patients not getting comprehensive services and some even waiting too long in queues. The purpose of this study was to provide information to the health center about the prediction of an increase in the number of patient visits that might occur in the future. The data used in this study were patient visit data at the IX Koto Sungai Lasi health center from 2019, 2020, and 2021 to extract the data that was obtained. The method used in this study was the Monte Carlo method. The results of the study can predict patient visit rates in the following years with an average accuracy rate of 91%, in 2020, and 85% in 2021, the results of these predictions can be a reference for the Puskesmas to take action and policies to improve quality of service at the Puskesmas.